Congenital laryngotracheoesophageal cleft masquerading as recurrent pneumonia - Vishrutha; H Ramesh; M Mohan; B M Harsha (Wolters Kluwer Medknow Publications, 2015)
Laryngotracheoesophageal cleft (LTEC) is a uncommon congenital malformation of the posterior part of the larynx, creating an abnormal communication between the laryngotracheal axis and the pharyngo- oesophageal axis. Tins condition manifest with non-specific respiratory symptoms, posing diagnostic challenge. Here we report a case of 75 days old infant with recurrent pneumonia and acute life threatening event manifested as milk aspiration. On endoscopic evaluation type 1 LTEC (Laryngeo trachea esophageal cleft) was diagnosed. Intervention/Outcome : Infant was managed conservatively and doing well on follow up.